Konsep Ummi Nabi Muhammad (S.A.W) dari Perspektif Al-Qur’an - Wan Ali, Wan Zailan Kamaruddin (Jurnal Usuluddin, 1998)
The aim of this article is to examine the concept of Ummi (illiteracy) as mentioned in the Holy Qur’an. It is among the issues discussed by the Muslim and non-Muslim scholars in relation to the prophethood of Muhammad (p.b.u.h) and to the miracle of the Qur’an. Here, the Ummi problem will also be examined in the light of two periods, before and after he (p.b.u.h) became a prophet and messenger as well as its position in relation to the hadith.